Suppression of IGF1R in Melanoma Cells by an Adenovirus-Mediated One-Step Knockdown System - Haoran Xin; Mingxing Lei; Zhihui Zhang; Jie Li; Hao Zhang; Xinwei Luo; Aoyun Wang; Fang Deng (Elsevier, 2018)
Abnormal activation of the IGF1R signaling pathway accelerates melanoma development and metastases. RNAi systems with complex cloning procedures and unsatisfactory efficiency in suppressing gene expression have become the technical difficulties that hinder their utility when studying gene knockdown. Here we established a simplified adenovirus-mediated gene knockdown system by which a single adenoviral vector carries multiple siRNA fragments that can effectively suppress IGF1R expression in melanoma cells. We first generated the adenovirus that simultaneously expresses three human or mouse siRNAs targeting IGF1R (AdRIGF1R-OK). qRT-PCR and immunofluorescence staining revealed that IGF1R expression was significantly decreased in the melanoma cells that were infected with AdRIGF1R-OK. Bioluminescence imaging showed that the size of the tumor formed by the xenografts infected with AdRIGF1R-OK was significantly smaller than that of the controls. Annexin V-FITC flow cytometry assay, immunofluorescence staining for cleaved caspase-3, and Hoechst staining showed that more cells underwent apoptosis after infection with AdRIGF1R-OK. Luciferase reporter assay, crystal violet cell viability assay, and cell-cycle analysis showed that the proliferation of melanoma cells infected with AdRIGF1R-OK was significantly decreased compared to the controls. This study demonstrates that the OK system is effective in silencing gene expression, with promising potential to treat melanoma and other diseases. Keywords: RNAi technology, gene therapy, melanoma, IGF1R, one-step knockdown system, adenovirus